One last summer - Spencer, Kate, 1979- (Forever, 2024)
"Clara Millen's life is spiraling out of control: her dream job is a nightmare, she's resoundingly single, and it's been years since she's taken some time off. Thankfully, the last problem she can fix - this year she'll join her friends on their annual summer vacation to their beloved childhood sleepover camp for a much-needed escape. But when Clara arrives at Pine Lake Camp, she faces yet another unwelcome change: the owners are retiring and selling the property. The news turns her plans for revelry into a night of reminiscing . . . and prompts a surprise heart-to-heart between Clara and Mack, her old camp nemesis and constant competitor, who's still just as annoying (and annoyingly handsome). Soon the campfires aren't all that's throwing off sparks. And when one wildly passionate night turns into two (then too many to count!), Clara begins to wonder if she and Mack could have a future together. But when Clara's boss finally offers her everything she's worked so hard for, Clara will need to decide if the life she's always wanted is the life that makes her feel truly alive"--